Moral philosophy and social ethics in nation building (2016)
Education is a major tool for the development of man intellectually and socially. To this end, this work discusses the importance of utilitarianism as a moral philosophy followed by the examination of social ethics such as altruism, justice and truth telling, as they relate to knowledge and development of social and moral values among learners. In a philosophical context, we examine the relevance of the principles of utilitarianism to nation building, implication of the reviewed work and conclusion as they affect different cadres of society educators and learners alike are presented